Educative career and associative practices of a Tucumana in between centuries: Margarita Todd, schoolteacher (2015)
During the early 20th century, the province of Tucumán attended an expansion process of diverse associative experiences among which the sociability environments linked to teaching and cultural worlds are stressed. Also, it is during this period that a change can be noticed in 19th century sociability practices that showed the predominance of an exclusively masculine sociability in the cultural and literary ields. Indeed, either in search of perfecting the tools obtained in their experience with academic institutions, or in pursuing the improvement of their work situation, several female teachers emerged in these environments which became a part of this structure of educational and cultural sociability. Certain that sociability practices constitute excellent points of observation for studying the scope of female participation in the public sphere, this work aims at reconstructing and analyzing the career of one of these teachers. Margarita Todd, who developed a successful career as a Tucumana teacher and was able to express some of the intellectual and cultural concerns of the time, in which scientiic knowledge was one of the perspectives to create a future provincial university.